2001
DOI: 10.1046/j.1365-3040.2001.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence and photochemical properties of phytochromes in wild‐type wheat and a transgenic line overexpressing an oat phytochrome A (PHYA) gene: functional implications

Abstract: Etiolated seedlings of wild-type wheat and a transgenic line overexpressing an oat PHYA gene were investigated by the use of in situ low-temperature fluorescence spectroscopy. The red-absorbing phytochrome form, Pr, was characterized by (1) fluorescence emission spectrum; (2) total phytochrome content, and (3) by the extent of the Pr → → → → lumi-R photoconversion at low temperature ( γ γ γ γ 1 ), and of the Pr → → → → Pfr photoconversion at ambient temperature ( γ γ γ γ 2 ) as derived from emission data. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Because the properties and relative content of the two phyA species in rice (WT seedlings and the phyB mutant) are very close to those of the two phenomenological phy pools (Pr′ and Pr′) in the WT monocots ( i.e. oat, wheat, barley and maize) (19–21), we believe it likely that the two phyA populations are present in all monocots.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Because the properties and relative content of the two phyA species in rice (WT seedlings and the phyB mutant) are very close to those of the two phenomenological phy pools (Pr′ and Pr′) in the WT monocots ( i.e. oat, wheat, barley and maize) (19–21), we believe it likely that the two phyA populations are present in all monocots.…”
Section: Discussionmentioning
confidence: 85%
“…We used low‐temperature fluorescence spectroscopy of phytochrome in etiolated tissues as a major experimental approach (16–21). The procedure of the rice seedlings growth, sample preparation and spectral measurements were essentially the same as those reported elsewhere (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental approach was the same as that used earlier (see [11][12][13][14]17,18,21,22] and the literature cited therein). To obtain the phytochrome parameters in the sample, low-temperature (85 K) emission spectra (wavelength of the excitation, k e , 610 or 650 nm) were taken under two different experimental settings (see Figs.…”
Section: Equipment and Measurement Proceduresmentioning
confidence: 99%
“…It was found that the major and light-labile phyA 0 is primarily responsible for the HIR and possibly VLFR during de-etiolation. The more light-stable minor phyA 00 may be functional in light-grown plants and may also modify the action of phyA 0 inhibiting its activity [10,17,18]. However, the exact nature of the two phyA forms and functional distinctions between them still remain obscure.…”
Section: Introductionmentioning
confidence: 99%